Pembelajaran Berbasis Proyek Mata Pelajaran Prakarya dan Kewirausahaan dengan Rangkaian LEAD (Listen, Explore, Analyze, and Do) untuk Menumbuhkan Adversity Quotient Berbantuan Mobile Learning Schoology - Titis Pandangwati; Saida Ulfa; Anselmus J. E. Toenlioe (Pascasarjana Universitas Negeri Malang, 2018)
Abstract: The development of project-based learning design with the LEAD series (Listen, Explore, Analyze and Do) aided the schoology to answer the problems of the subjects of workshop and entrepreneurship which aimed to print the students as entrepreneur owner. The research method used to develop the learning design is Dick, Carey and Carey (2015). Based on the validation percentage of 91.25% material experts, 90% design learning experts, and 97.5% of media experts, field trials of 92.83% means that instructional design and instructional media are appropriate for learning. While the results of effectiveness test all test subjects as many as 30 including Adversity Quotient categories are climbers.  Abstrak: Pengembangan desain pembelajaran berbasis proyek dengan rangkaian LEAD (Listen, Explore, Analyze, and Do) berbantu schoology untuk menjawab permasalahan mata pelajaran prakarya dan kewirausahan yang bertujuan mencetak peserta didik sebagai owner entrepreneur. Metode penelitian yang digunakan untuk mengembangkan desain pembelajaran yaitu Dick, Carey and Carey (2015). Berdasarkan hasil validasi persentase ahli materi 91.25%, ahli desain pembelajaran 90%, dan ahli media 97.5%, uji coba lapangan 92,83% artinya desain pembelajaran dan media pembelajaran layak digunakan dalam pembelajaran. Sementara itu, hasil uji efektivitas seluruh subjek uji coba sebanyak 30 termasuk kategori Adversity Quotient yaitu climbers.